Anti-SARS-CoV-2 Inhibitory Profile of New Quinoline Compounds in Cell Culture-Based Infection Models - Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2021)
The presently ongoing pandemic of human SARS-CoV-2 infections (COVID-19) presents an enormous challenge in surveillance, vaccine and antiviral drug development. Here we report the synthesis of new bioactive quinoline-morpholine hybrid compounds and their virological evaluation, which proves pronounced cell culture-based inhibitory profile against SARS-CoV-2. Thus, selected quinoline compounds may suggest specific hit-to-lead development.
CRIS-Team WoS Importer:2022-01-07